ATP release during cell swelling activates a Ca2+-dependent Cl− current by autocrine mechanism in mouse hippocampal microglia - E. Murana (Nature Portfolio, 2017)
Abstract Microglia cells, resident immune cells of the brain, survey brain parenchyma by dynamically extending and retracting their processes. Cl− channels, activated in the cellular response to stretch/swelling, take part in several functions deeply connected with microglia physiology, including cell shape changes, proliferation, differentiation and migration. However, the molecular identity and functional properties of these Cl− channels are largely unknown. We investigated the properties of swelling-activated currents in microglial from acute hippocampal slices of Cx3cr1 +/GFP mice by whole-cell patch-clamp and imaging techniques. The exposure of cells to a mild hypotonic medium, caused an outward rectifying current, developing in 5–10 minutes and reverting upon stimulus washout. This current, required for microglia ability to extend processes towards a damage signal, was carried mainly by Cl− ions and dependent on intracellular Ca2+. Moreover, it involved swelling-induced ATP release. We identified a purine-dependent mechanism, likely constituting an amplification pathway of current activation: under hypotonic conditions, ATP release triggered the Ca2+-dependent activation of anionic channels by autocrine purine receptors stimulation. Our study on native microglia describes for the first time the functional properties of stretch/swelling-activated currents, representing a key element in microglia ability to monitor the brain parenchyma.